Lauver Family Farms: utilizing the Conservation Reserve Program as a risk management tool - Lauver, Andrew James (Kansas State University, 2017)
For five generations, Lauver Family Farms has been founded upon faith, family, and farming near Rockwell City, IA. It is these core principles and beliefs that drive everyday actions through conservation minded decisions, community involvement, and a passion for the land. Presently, the farm is operated by Grandfather Don Lauver, Father Kevin Lauver, and sons Andrew and Jacob Lauver. The Lauver Family Farm was originally purchased in 1942 by Joseph Gordon, who at his peak held 700 acres in his name. In 1945 Glen and Viola Lauver purchased what is now Lauver Family Farms, located on the Des Moines Lobe land region of Iowa. The Des Moines Lobe is a glacial lobe encompassing rich, heavy soils with high organic matter, requiring dredge ditches and tiling in many areas. Through a commitment to conservation, corn and soybean acres are rotated annually. With regard to corn cultivation and planting practices, soybean stubble is field cultivated once, followed by planting. On soybean ground, the corn stalks are disk ripped, and then field cultivated twice before planting soybeans. The goal is to minimize trips through the field by exhibiting these conservation tillage practices. If land has much slope or erosion potential, then it is only disked and then planted. Currently, the farm is comprised of 400 acres of row crops and 50 acres of wetland, 30 acres on the Home Farm and 20 acres on the Obye Farm, enrolled in the Conservation Reserve Program in 2002. Kevin and Don Lauver, the primary decision makers, requested an analysis of the environmental and economic impact of the Conservation Reserve Program on the farm. By taking acres out of production for at least 10 to 15 years that perennially drown due to often wet soil conditions, they will be able to utilize the Conservation Reserve Program as a risk management tool. Now, Lauver Family Farms is faced with a decision to determine if a 10 or 15 year enrollment in the Conservation Reserve Program has the greatest economic and environmental return, since the current enrollment expires in 2016. Procedures and methods were established to meet the purpose of this thesis to determine which option was the most profitable long-term for the operation. The purpose includes evaluating the sources of data relevant to Lauver Family Farms decision by utilizing decision tools to make a collective decision on the future of the farmland and opportunity costs analyzed. Lauver Family Farms’ objective for this project was to determine how the Conservation Reserve Program provides a return on the investment of the decision to re-enroll, or even enroll more acres in the program. This analysis will be used each time an enrollment decision must be made, and will be of significant importance as sons Andrew and Jacob Lauver make management decisions in the years to come.
Keywords: Conservation Reserve Program; CRP; Farm Management